Answer:
1. L1 = ![\frac{L2}{X(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%7D%7BX%28O2%20-O1%29%7D)
2. O2 = ![\frac{L2 - L1(1 + XO1)}{XL1}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%281%20%2B%20XO1%29%7D%7BXL1%7D)
Step-by-step explanation:
Given: x = ![\frac{L2 - L1}{L1(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%7D%7BL1%28O2%20-O1%29%7D)
1. To make L1 the subject of formula;
x = ![\frac{L2 - L1}{L1(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%7D%7BL1%28O2%20-O1%29%7D)
cross multiply to have;
L2 - L1 = xL1(O2 - O1)
collect like terms,
L2 = xL1(O2 - O1) + L1
factorize the right hand side;
L2 = L1[x(O2 - O1)]
L1 = ![\frac{L2}{X(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%7D%7BX%28O2%20-O1%29%7D)
2. To make O2 the subject of formula;
x = ![\frac{L2 - L1}{L1(O2 -O1)}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%7D%7BL1%28O2%20-O1%29%7D)
cross multiply to have;
L2 - L1 = xL1(O2 - O1)
open the bracket to have;
L2 - L1 = xL1O2 - xL1O1
⇒ xL1O2 = L2 - L1 + xL1O1
O2 = ![\frac{L2-L1 + XL1O1}{XL1}](https://tex.z-dn.net/?f=%5Cfrac%7BL2-L1%20%2B%20XL1O1%7D%7BXL1%7D)
= ![\frac{L2 - L1(1 + XO1)}{XL1}](https://tex.z-dn.net/?f=%5Cfrac%7BL2%20-%20L1%281%20%2B%20XO1%29%7D%7BXL1%7D)
Answer:
Radius: 4
Center: (-5,4)
Step-by-step explanation:
To find the radius, you take the square root of what the equation is equal to (in this case that is 16)
To find the center, you set what is in the parenthesis equal to 0 so:
x+5=0 becomes x=-5
y-4=0 becomes y=4
Hope this helped!
7(y+2)=3
seven times the sum of a number (y) and 2
means y+2 multiplying by 7
Answer:
42.40705%
Step-by-step explanation:
(1 - (23/100)^(19/9) = 1 + r/100
0.57593 = 1 + r/100
r = 42.40705%